PENGARUH TURBOCHANGER TERHADAP DAYA MOTOR BAKAR PADA MESIN YANMAR MODEL 495-T 4 SILINDER 350 PS - Hodmiantua Sitanggang,S.T, M.M; Enzo Wiranta Battra Siahaan,S.T,M.T (Universitas Quality, 2021)
Along with the increasingly rapid development of science and technology, this will encourage every manufacturer or industry to develop its invention technology, for example, in the field of Automotive Technology which is experiencing a fairly rapid development. To get to the above, of course, an additional device is needed, one of which is by using a turbocharger. The turbocharger is a mechanism for supplying air with a density that exceeds the density of atmospheric air into the cylinder to be pressed in the compression stroke so that the motor power will increase. To get the effect of using a turbocharger, it can be done by conducting direct testing of the Yanmar Model 495-T 4 cylinder 350 PS engine with a variable rotation of 1300 rpm, 1700 rpm, 2100 rpm, 2500 rpm, 2900 rpm, and recording changes in the load on the dynamometer, internal temperature. space, radiator water temperature, lubricant pressure, air pressure coming out of the compressor, fuel consumption time per 50 cc. So that the results of the test show that the specific fuel consumption is 106 gr / hp-hr, while for a diesel motorbike without a turbocharger the specific material consumption is 126 gr / hp-hr, therefore the specific fuel consumption of a diesel motorbike using a turbocharger decreases by 15.87%. and the average effective pressure increases at the effective power (Ne) which is 152 hp, while for a diesel motorbike without a Turbocharger the effective power (Ne) produced is 110 hp so that the percentage increase in power obtained is 42%.